Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
Negative Two.
Alright, buckle up, buttercup. Two thirds to the negative 2 power equals 9 over 4. Why? Because negative exponents mean you flip the fraction and make the exponent positive. So, 2/3 to the power of -2 becomes 3/2 squared, which simplifies to 9/4. Math can be a wild ride, but hey, that's the beauty of numbers!
-2*(-2)2 + 0*(-2) + 9 = -2*4 + 9 = -8 + 9 = 1
1155
Negative sixty-four minus four squared is equal to -80.
Because in parenthesis you have to multiply it by something.
negative 2
first, you square negative 4. Since negative times negative is positive, then you get positive sixteen., Then positive 16 times two is 32
Four!
-22 = 4
x < 2 or x > 8.
54.3 squared
Four
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
(-4)2 - 4 = 12
FOUR